2005
DOI: 10.1188/05.onf.97-104
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Experience and the Care of Dying Patients

Abstract: Developing continuing education programs that teach effective coping strategies to prevent death anxiety and identifying barriers that can make caring for dying patients difficult may make the journey from novice to expert nurse a gratifying and rewarding experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
139
3
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 9 publications
13
139
3
14
Order By: Relevance
“…The findings of the present study confirm earlier findings of Dunn et al [13], Feudtner et al [14] and Lange et al [11] that used even larger samples. Frequent exposure will tend to reduce the anxiety level of the nurse while attending to the critically sick patient and his family.…”
Section: Length Of Time Spent In Cancer Wardsupporting
confidence: 83%
“…The findings of the present study confirm earlier findings of Dunn et al [13], Feudtner et al [14] and Lange et al [11] that used even larger samples. Frequent exposure will tend to reduce the anxiety level of the nurse while attending to the critically sick patient and his family.…”
Section: Length Of Time Spent In Cancer Wardsupporting
confidence: 83%
“…In general, it can be implied that experiences with death improve attitudes towards care of the dying among nurses, but not in significant amounts. Our results also disagreed with a study done by Dunn et al 8 who found that positive attitudes and care are associated with more experience of taking care of dying patients. Thus, nurses who have more years of experience and more personal experiences with dying patients will be better suited to care for the dying patient.…”
Section: Discussioncontrasting
confidence: 57%
“…Results showed that there was significant relationship between attitudes score with age. Dunn et al 8 found that positive attitudes and care are associated with more experience and age in taking care of dying patients. Thus, nurses who have more years of experience and more years of working with dying patients will be better suited to care for the dying patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in Spain showed that there was no relationship between attitudes in caring dying patients and gender factor (Edo-Gual, Tomás-Sábado, Gómez-Benito, Monforte-Royo, & Aradilla-Herrero, 2017). However, Dunn, Otten, and Stephens (2005) explains that feminism influences the attitudes of caring for dying patients.…”
Section: Resultsmentioning
confidence: 99%